Abnormal excessive per vagina (PV) bleeding on Esmya–selective progesterone receptor modulator (SPRM) in a symptomatic patient with uterine fibroid. (14th May 2015) - Matytsina-Quinlan, Lyubov; Matytsina, Laura
Abstract : A woman in her late 40s presented with excessive per vagina (PV) bleeding and uterine fibroid. She reported excessive PV bleeding after starting Esmya; she was brought in by ambulance to the emergency department with profuse bleeding. Abnormal uterine bleeding (AUB) developed after selective progesterone receptor modulator (SPRM) administration in this symptomatic patient with uterine fibroid. The drug was withheld and surgical treatment considered. Progressive deterioration of PV bleeding after receiving SPRM led to an urgent laparoscopic total hysterectomy, which had to be postponed due to severe anaemia. Surgery took place regardless because the excessive bleeding continued. Histology revealed a 6 cm submucosal uterine fibroid (SMUF) and adenomyosis. Physicians prescribing SPRMs to stop PV bleeding should be aware of potential AUB, which could lead to urgent hysterectomy. The mechanism of action of SPRMs is not clearly understood. Awareness of the side effects of Esmya, such as AUB, must be kept in mind when administering SPRMs.